- #1

- 3

- 0

-cos(60) = cos(-60) = cos(300) = cos(60)

- Thread starter The_Prime_Number
- Start date

- #1

- 3

- 0

-cos(60) = cos(-60) = cos(300) = cos(60)

- #2

- 92

- 0

cos(-x) = cos(x) ( cos is an even function )

If you draw these angles over the unit circle, then cos(x) refers to the x component of where the ray intersects the circle. For 60 degrees and -60 degrees, the x component lies to the right of the y axis, so both are positive (and equal).

- #3

- 3

- 0

Ok, thanks for clearing that up for me.

- Last Post

- Replies
- 28

- Views
- 867

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 6

- Views
- 7K

- Last Post

- Replies
- 1

- Views
- 502

- Last Post

- Replies
- 3

- Views
- 6K

- Last Post

- Replies
- 8

- Views
- 581

- Replies
- 6

- Views
- 537

- Replies
- 1

- Views
- 3K

- Replies
- 2

- Views
- 6K

- Replies
- 13

- Views
- 1K